RESEARCH OUTCOMES OF REVERBERATION OF STEEL FIBERS ON DYNAMIC MECHANICAL PROPERTIES - Kewal Singh, Kanwal Jit Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
With the advancement of current construction technology, a wide range of complicated structures with cement concrete performance requirements have evolved; as a result, researchers are continually looking for ways to improve the performance of concrete. Highstrength or even ultrahigh-strength concrete is in considerable demand right now, because to its low cost and ease of building. High-strength concrete (HSC) is a typical example of concrete of the high-tech period; yet, it is more fragile than regular concrete, and damage often happens unexpectedly. Many dangerous aspects are undoubtedly introduced to huge and complicated concrete constructions.